Commitment Beyond Proximity: Exploring Experiences of Organizational Commitment in Remote Work Settings - Höyhtyä, Hilla (2025)
This study examines how remote working affects employees’ experiences of Meyer and Allen’s (1991) three components of commitment: affective, continuance and normative commitment. This is investigated through semi-structured interviews with employees in a Finnish organization that offers varying degrees of remote work flexibility. The findings suggests that although active virtual communication in group chats may help sustain a sense of community and belonging, remote work challenges affective commitment due to reduced social interaction and by changing the nature of these interactions. Continuance commitment, however, seems unimpacted since remote work is increasingly experienced as a baseline expectation. The study highlights that remote work increases normative commitment and a sense of reciprocity, when it’s organized in a way that it communicates trust. Consequently, offering autonomy through trust-based leadership is seen as a key element for fostering normative commitment. Furthermore, the study emphasizes the importance of complementing active virtual communication with regular face-to-face interactions to maintain affective commitment among remote workers. Keywords: organizational commitment, three component commitment model, remote work, organizational behavior